Pengaruh Brand Awareness dan Brand Trust terhadap Keputusan Pembelian Sabun Lifebuoy di Dusun II Namo Pinang Keamatan Sibiru-Biru - Marsela, Nia; Aramita, Finta (Economics, Business and Management Science Journal, 2025)
This study aims to analyze the influence of Brand Awareness and Brand Trust on the purchase decision of Lifebuoy Soap in Hamlet II Namo Pinang, Sibiru-Biru District. The population used in this study is consumers of Lifebuoy Soap in Hamlet II Namo Pinang, Sibiru-biru District. This study used 86 respondents with statistical analysis including validity tests, reliability, classical assumptions, multiple linear regression, t-test, f test, and determination coefficient (R²) using SPSS 25. Data were obtained from primary and secondary sources through questionnaires. The results of the study show that Brand Awareness and Brand Trust have a positive and significant effect on purchase decisions. Brand Awareness has a t-count t-table (4,179 1,663) with a significance of 0.001 0.05, while Brand Trust has a t-count t-table (10,383 1,663) with a significance of 0.000 0.05. The F-test shows the F-count F-table (54,906 3.95), so that the two variables have a simultaneous effect on the purchase decision. The results of this study show that Brand Awareness and Brand Trust have a significant role in the purchase decision of Lifebuoy soap. Therefore, companies can improve their marketing strategies by strengthening their brand image and building consumer trust through educational campaigns and customer testimonials.